CINÉTICA DE LA INFECCIÓN POR Brucella ovis EN CARNEROS DURANTE UNA ÉPOCA DE EMPADRE - Quispe Ch., Rocío (2002)
The evolution of Brucella ovis infection was documented clinically and serologically in a flock of 250 field reared rams from a large sheep production company in the central sierra of Peru. Although no clinical evidence of Brucellosis (epididymitis) was detected at the start of a 2-month breeding campaign, 58.7 of the animals were positive to the indirect ELISA test. At the end of the breeding season, 74.4% tested positive using indirect ELISA and 28.4% of the animals had to be eliminated due to testicular lesions. These results demonstrate rapid evolution of the bacterial infection from seropositive to clinical manifestation, indicating that reliance on clinical observation alone is insufficient to control the infection under field conditions. Serological testing is necessary in order to identify and eliminate all positive reactors. If this procedure is not followed, alternative control alternatives such as vaccines should be employed to control the disease.